2021
DOI: 10.21608/jpp.2021.178930
|View full text |Cite
|
Sign up to set email alerts
|

The Role of New Transformants Phosphate Bio-Stimulates (PBS) Bacteria Inoculates on Growth, Yield and Quality of Kohlrabi Plants

Abstract: Producing new transformants phosphate bio-stimulate (PBS) bacterial inoculates in addition to study their potential effect on growth, yield and quality of kohlrabi plants at two successive seasons 2017/2018 and 2018/2019 were studied in this present work. The obtained results revealed that using the three tested phosphate bio-stimulate inoculates (PBS1, PBS2 and PBS3) alone or combined with different doses of phosphate mineral fertilizer PMF (calcium superphosphate) increase considerably growth, yield and qual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, in the case of inoculation with bacteria, both B1 and B2 combined with the mixed water + S treatment increased the absorption of all macronutrients, equaling, in most cases, the values of control plants (Table 3). These findings are in harmony with those reported by Soltan et al [1], who observed increases in N, P, K, and Mg, as the bacteria increased the availability of nutrients required by the plants. The nutritional effect of Pantoea can be ignored, as it does not affect the absorption of N and P [8].…”
Section: Mineral Contentsupporting
confidence: 91%
See 3 more Smart Citations
“…However, in the case of inoculation with bacteria, both B1 and B2 combined with the mixed water + S treatment increased the absorption of all macronutrients, equaling, in most cases, the values of control plants (Table 3). These findings are in harmony with those reported by Soltan et al [1], who observed increases in N, P, K, and Mg, as the bacteria increased the availability of nutrients required by the plants. The nutritional effect of Pantoea can be ignored, as it does not affect the absorption of N and P [8].…”
Section: Mineral Contentsupporting
confidence: 91%
“…Among the species that are part of the Brassicaceae family, we find kohlrabi (Brassica oleracea var. gongylodes), which has a short growing period in early summer and autumn [1]. The most consumed part of kohlrabi is the fleshy, swollen stem (bulb), which can be eaten raw, cooked, or preserved.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To do this, this study will be carried out on kohlrabi plants, which belong to the Brassicaceae family. It is a vegetable with great nutritional value due to its high content of antioxidants such as vitamin C, glucosinolates, phenolic compounds and nutrients such as potassium, which have anti-inflammatory, antioxidant and anti-cancer properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%